The Unfolded Protein Response and Diabetic Retinopathy - Ma, Jacey Hongjie (J Diabetes Res, 2014)
Diabetic retinopathy, a common complication of diabetes, is the leading cause of blindness in adults. Diabetes chronically damages retinal blood vessels and neurons likely through multiple pathogenic pathways such as oxidative stress, inflammation, and endoplasmic reticulum (ER) stress. To relieve ER stress, the cell activates an adaptive mechanism known as the unfolded protein response (UPR). The UPR coordinates the processes of protein synthesis, protein folding, and degradation to ensure proteostasis, which is vital for cell survival and activity. Emerging evidence suggests that diabetes can activate all three UPR branches in retinal cells, among which the PERK/ATF4 pathway is the most extensively studied in the development of diabetic retinopathy. X-box binding protein 1 (XBP1) is a major transcription factor in the core UPR pathway and also regulates a variety of genes involved in cellular metabolism, redox state, autophagy, inflammation, cell survival, and vascular function. The exact function and implication of XBP1 in the pathogenesis of diabetic retinopathy remain elusive. Focusing on this less studied pathway, we summarize recent progress in studies of the UPR pertaining to diabetic changes in retinal vasculature and neurons, highlighting the perspective of XBP1 as a potential therapeutic target in diabetic retinopathy.